(3GdLhgQI GdeVjI (B_ (3CQLhRIs
(3ChdgG (B:s
(3GdMeO ddg eHOF GdOGHQGJ hef GfTG HMceJg EJbGf eGUfYG abSe GdOgQ CbSGekG hCdgefG JMbjb YR GdPi CfTGg hGNJQYG s
(3BNQgG (B:s
(3jGhKdK MchG ai YbQH hcPG JLOg ai GdMhJ CfTGg GdPi aQYG Ke GdUdGI Ydi NjQ GdCfGe hef gOi Edi GdQTO hGdEjeGf Mjf OYG JeJ GdLhgQI GdeVjI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B16(3H (B- (3U(B17(3Cs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3482( 4) (3C(B) s
Keywords: (3Gdadcs